Perceptual Organization in Colour Perception: Inverting the Gamut Expansion Effect. (August 2013) - Ekroll, Vebjørn; Faul, Franz
In the well-known gamut expansion effect, uniformly coloured target patches are perceived as more colourful when they are embedded in a uniform grey surround than when they are embedded in a variegated one. Here, we provide a demonstration showing that this effect can be inverted when the uniformly coloured target patches are replaced by variegated ones. This observation suggests that the gamut expansion effect is due to mechanisms of transparency perception rather than due to contrast adaptation.